Nanoindentation of Graphene-Reinforced Silica Aerogel: A Molecular Dynamics Study - Sandeep P. Patil (Molecules, 2019)
In the present work, we performed nanoindentation tests using molecular dynamics (MD) simulations on graphene, native silica aerogels, and single- and multi-layered graphene-reinforced silica aerogel nanocomposites. This work mainly focused on the two aspects of nanoindentation simulations: first, the resultant indentation force–depth curves, and second, the associated mechanical deformation behavior. We found that in the single-layer graphene-reinforced silica aerogel nanocomposite, the indentation resistance was four-fold that of native silica aerogels. Moreover, the combined system proved to be higher in stiffness compared to the individual material. Furthermore, the indentation resistance was increased significantly as we proceeded from single- to two-layered graphene-reinforced silica aerogel nanocomposites. The results of the study provide a detailed understanding of the mechanical behavior during the indentation tests of nanocomposites, which helps to design advanced nanoscale multi-layered materials.